Distinct relative abundances in pathogens detected in mechanically ventilated patients with suspected pneumonia in the intensive care unit at King Abdulaziz University Hospital - Haifa Algethamy; Diyaa H. Bokhary; Ibrahim Abushoshah; Abdulrahman A. Alalyani; Maan K. Baamer; Dalya M. Attallah; Ruba M. Alotaibi; Shehla N. Amin; Shaza A. Mass; Nisreen R. Tashkandy (Scientific Reports)
Abstract In this study, we present for the first time the landscape of the lung microbiota in patients with ventilator-associated pneumonia in Intensive Care Units in Saudi Arabia. DNA from 83 deep endotracheal aspirate lung samples was subjected to PacBio sequencing to identify pathogens in comparison with conventional diagnostic techniques. Patients on ventilation with pneumonia presented with similar lung flora to those of patients on ventilation without pneumonia. Proteobacteria, Firmicutes, and Bacteroidetes were detected in the majority of the samples. Samples treated with different antibiotics exhibited similar abundances of phyla and families. In order, the ten most common species detected in 16 clusters were Klebsiella pneumoniae, Stenotrophomonas maltophilia, Haemophilus influenzae, Pseudomonas aeruginosa, Metamycoplasma salivarium, Elizabethkingia anophilis, Staphylococcus aureus, Acinetobacter baumannii, Prevotella oris and Klebsiella africana. Of 51 on ventilation with pneumonia, the pathogens identified through sequencing corresponded with the findings from culture-dependent tests in 26 patients (50.98%), whereas the results differed in 30 patients (58.82%). Of 32 patients on ventilation without pneumonia, the pathogens identified through sequencing matched the conventional diagnostics results in only two patients (6.25%) but differed in 25 patients (78.13%). In summary, patients on mechanical ventilation with pneumonia did not display notable phenotypic traits. K. pneumoniae and S. maltophilia were the most common taxa detected in the samples, although some variations in microbial composition were observed. We conclude that Intensive Care Units exhibit distinct patterns of microbial colonization.